Simultaneous aerobic and anaerobic respiration in hot spring chemolithotrophic bacteria - Lisa M. Keller; Daniel R. Colman; Eric S. Boyd (Nature Communications)
Abstract Aerobic and anaerobic organisms and their functions are spatially or temporally decoupled at scales ranging from individual cells to ecosystems and from minutes to hours. This is due to competition for energy substrates and/or biochemical incompatibility with oxygen (O2). Here we report a chemolithotrophic Aquificales bacterium, Hydrogenobacter, isolated from a circumneutral hot spring in Yellowstone National Park (YNP) capable of simultaneous aerobic and anaerobic respiration when provided with hydrogen (H2), elemental sulfur (S0), and O2. Cultivation experiments demonstrated that simultaneous aerobic and anaerobic respiration enhanced growth rates and final cell concentrations when compared to those grown aerobically or anaerobically. Consumption of O2 measured via gas chromatography and detection of transcripts for proteins involved in S0 and O2 reduction in H2/S0/O2-grown cultures confirmed co-occurring aerobic and anaerobic metabolism. This aerobic, S0-reducing metabolism is suggested to provide a competitive advantage in environments where O2 availability is low and variable. Genomic data indicating the prevalence of proteins allowing for this hybrid form of energy metabolism among bacteria and archaea suggest it to be widespread but previously overlooked due to rapid, O2-dependent abiotic oxidation of produced sulfide. These observations challenge existing paradigms of strict delineations between aerobic and anaerobic metabolism.